DOES STORYTELLING CAPTIVATE STUDENTS IN ICE-BREAKING SESSIONS?: ENGLISH FOR SPECIFIC PURPOSES STUDENTS’ PERCEPTION - Ni Kadek Herna Lastari; Made Yudyantara Risadi; I Putu Yoga Laksana (IKIP Siliwangi, 2024)
An attractive yet meaningful activity needs to be conducted as an ice-breaking activity in an ESP class to build a conducive learning environment that relaxes the students. This study aimed to figure out whether storytelling can engage vocational students in tertiary education in an ice-breaking session and the perception of the students. This study employed A qualitative research design involving 51 purposively chosen participants from the English for Specific Purposes class. Observation was carried out and followed by a Focus Group Discussion. The study revealed that the students were entertained by listening to fascinating and unusual stories from the storytellers because the students could capture positive enlightenment in their minds. The students became impatient to attend the ice-breaking session since, after the storytelling, their confidence in speaking was realized to be improved. Although storytelling could captivate the students' attention, lack of vocabulary range, audience engagement, and anxiety were unveiled as obstacles. The topic of destination visits, memorable experiences, and personal growth are the students' favorite. In the future, the students might have both free topics or specific topics regarded to the lesson for storytelling as the ice-breaking to keep the students entertained yet learn something advantageous.